DNA methylation: gene expression regulation - Zmarzły, Nikola; Wojdas, Emilia; Skubis, Aleksandra; Sikora, Bartosz; Mazurek, Urszula (Acta Universitatis Lodziensis. Folia Biologica et Oecologica, 2016)
Epigenetic modifications are responsible for the modulation of gene expression without affecting the nucleotide sequence. The observed changes in transcriptional activity of genes in tumor tissue compared to normal tissue, are often the result of DNA methylation within the promoter sequences of these genes. This modification by attaching methyl groups to cytosines within CpG islands results in silencing of transcriptional activity of the gene, which in the case of tumor suppressor genes is manifested by abnormal cell cycle, proliferation and excessive destabilization of the repair processes. Further studies of epigenetic modifications will allow a better understanding of mechanisms of their action, including the interdependence between DNA methylation and activity of proteins crucial to the structure of chromatin and gene activity. Wider knowledge of epigenetic mechanisms involved in the process of malignant transformation and pharmacological regulation of the degree of DNA methylation provides an opportunity to improve the therapeutic actions in the fight against cancer.